ENVIRONMENTAL SAVING ANALOGY FROM PLASTIC WASTE AT SUPER INDO SUPERMARKET: A HINDU DIDACTIC REVIEW - Fetty Ngatmianingsih (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2019)
The mandatory charge imposed on the customers for single-used plastic bag (KPTG) as an effort to converse the environment from plastic waste, which has been done by Super Indo supermarket, is a positive action towards the company’s sustainability strategy. This action goes along with Hindu didactic to have better life such as Canakya Nitisastra XIV, Tri Hita Karana, conserve the environment Sad Kertih, and balance of Bhuana Alit-Agung and Panca Sraddha. Observation and interviews with natural setting (management, store associates and customers) were conducted for this research at five chains of Super Indo